2018
DOI: 10.1111/den.13259
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter feasibility study of bowel preparation with castor oil for colon capsule endoscopy

Abstract: Bowel preparation with castor oil was effective for improving capsule excretion rate and reducing liquid loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 35 publications
1
41
1
Order By: Relevance
“…This highlights the importance of proper bowel preparation to visualize the complete colonic system and to properly compare CCE and colonoscopy. Some studies have investigated the effect of alternative bowel preparation regimens, and a recent study by Ohmiya et al reported that castor oil in addition to polyethylene glycol increased capsule excretion rates from 81% to 97 %, and reduced total examination time from 239 minutes to 201 minutes [28].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of proper bowel preparation to visualize the complete colonic system and to properly compare CCE and colonoscopy. Some studies have investigated the effect of alternative bowel preparation regimens, and a recent study by Ohmiya et al reported that castor oil in addition to polyethylene glycol increased capsule excretion rates from 81% to 97 %, and reduced total examination time from 239 minutes to 201 minutes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested low dose CaO (30 mL) has similar laxative efficacy of cleaning colon to bisacodyl (16). Moreover, studies (26, 27) also showed that 30 mL of CaO can reduce volume of preparation of bowel preparation solutions. And thus, we designed a regime of 2 L split PEG with 30 mL CaO to perform bowel preparation before colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…CaO has a high content of the hydroxylated unsaturated fatty acid ricinoleic acid (43), and it has been demonstrated that released ricinoleic acid has the ability of inducing strong laxative effect by activating small-intestinal smooth-muscle cells via the EP3 prostanoid receptor (44). Moreover, CaO will not cause serious side effects (27), and thus it has been used as a safe stimulant laxative in many settings (1416) except for pregnant women (45). Evidence suggested low dose CaO (30 mL) has similar laxative efficacy of cleaning colon to bisacodyl (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, colon capsule endoscopy was approved for reimbursement under the . Therefore we discussed it about the improvement of the discharge rate using castor oil [9], but were more likely to mistake a grease spot for polyps at interpretation because the castor oil was oil. However, because could reduce quantity of the castor oil by using Elobixibat and the lactulose which used this time, and, as for the intestinal tract irrigation degree, even which case was good, using in future this method is thought to be able to examine it.…”
Section: Discussionmentioning
confidence: 99%